Advancing measurements of tropospheric NO2 from space: New algorithm and first global results from OMPS. Issue 13 (10th July 2014) - Yang, Kai; Carn, Simon A.; Ge, Cui; Wang, Jun; Dickerson, Russell R.
Abstract We present a new algorithm based on the iterative spectral fitting technique for direct retrieval of nitrogen dioxide (NO2) vertical columns from hyperspectral satellite measurements, and a new spatial technique for separating the stratospheric and tropospheric contributions to the total NO2 vertical columns. This direct vertical column fitting (DVCF) algorithm allows more complete treatment of underlying algorithm physics compared to the differential optical absorption spectroscopy technique and enables more accurate accounting for the effects of spectral and altitude variations in NO2 measurement sensitivities. This DVCF algorithm and the stratosphere‐troposphere separation scheme are applied to ultraviolet measurements from the Nadir Mapper of the Ozone Mapping and Profiler Suite (OMPS) on the Suomi National Polar‐orbiting Partnership spacecraft. The first results demonstrate the potential of OMPS for sensitive global monitoring of tropospheric NO2. Comparisons show good agreement with Aura Ozone Monitoring Instrument (OMI) tropospheric NO2 data and that OMPS data have sufficient quality to continue and extend OMI NO2 data records.